2010
DOI: 10.1017/s1751731109991364
|View full text |Cite
|
Sign up to set email alerts
|

Production performance and pattern of milk fat depression of high-yielding dairy cows supplemented with encapsulated conjugated linoleic acid

Abstract: Several processes have been suggested to protect lipids from bioactivity of the rumen microorganisms. The majority of experiments with conjugated linoleic acid (CLA) were conducted using calcium salts of CLA. The objectives of this study were to determine the effects of encapsulated CLA (E-CLA) that was supplemented during days 21 to 100 post partum (PP), on milk fat depression, recovery rate and performance parameters. Forty-two multiparous Israeli-Holstein cows were divided at day 21 PP into two treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
4
19
4
2
Order By: Relevance
“…Further, CLA led to a decrease in the milk fat yield by 17.1% in period 2 in early lactation [20]. This is in accordance with data from the study by Moallem et al [30], in which 4.7 g/d t 10, c 12-CLA and 4.7 g/d c 9, t 11-CLA of the same lipid-encapsulated supplement was used and showed similar reductions in milk fat content (13%) and milk fat yield (9%, insignificant) compared to period 1 of the present study. Further, our results are also supported by observations from Giesy et al [31], who reported a reduction in milk fat content of approximately 14% by supplementing four CLA isomers as a mixture that, amongst other CLA isomers, contained 4.4 g/d or 8.6 g/d of t 10, c 12-CLA.…”
Section: Discussionsupporting
confidence: 88%
“…Further, CLA led to a decrease in the milk fat yield by 17.1% in period 2 in early lactation [20]. This is in accordance with data from the study by Moallem et al [30], in which 4.7 g/d t 10, c 12-CLA and 4.7 g/d c 9, t 11-CLA of the same lipid-encapsulated supplement was used and showed similar reductions in milk fat content (13%) and milk fat yield (9%, insignificant) compared to period 1 of the present study. Further, our results are also supported by observations from Giesy et al [31], who reported a reduction in milk fat content of approximately 14% by supplementing four CLA isomers as a mixture that, amongst other CLA isomers, contained 4.4 g/d or 8.6 g/d of t 10, c 12-CLA.…”
Section: Discussionsupporting
confidence: 88%
“…The mechanisms behind this effect are not yet understood, but seem to be regulated at the metabolic level since the CLA-containing supplements were consumed completely by all cows. In the trial of Moallem et al (2010), DMI was reduced significantly by 2.5% after the dietary supplementation of 5 g trans-10, cis-12 CLA and the authors supposed a relation with the saturation of the fatty acids in the diet. With the energy content of feed being nearly similar, the significantly lower net energy intake of the CLA-groups during the first weeks of lactation can be explained by the lower DMI of these animals in this time.…”
Section: Discussionmentioning
confidence: 96%
“…However, data regarding the long-term effects of CLA supplementation on dairy cows is still rare as most examinations were conducted either during the transition period and early lactation (Moore et al 2004;Selberg et al 2004;Castaneda-Gutierrez et al 2005;Odens et al 2007) or during a few weeks in mid lactation (Giesy et al 2002;de Veth et al 2005;Suksombat and Chullanandana 2008;Piamphon et al 2009;Sippel et al 2009;Moallem et al 2010). Only Perfield et al (2002) and Bernal-Santos et al (2003) performed studies over a 20-week period of lactation treatment, but their CLA supplement was a mixture of four isomers, including trans-8, cis-10 CLA; cis-9, trans-11 CLA; trans-10, cis-12 CLA; and cis-11, trans-13 CLA.…”
Section: Discussionmentioning
confidence: 99%
“…Pappritz et al, 2011;von Soosten et al, 2011), stimulating (Shingfield et al, 2004), as well as no effects (Perfield et al, 2002;Bernal-Santos et al, 2003;Castañeda-Gutiérrez et al, 2005;Odens et al, 2007;von Soosten et al, 2011) on DMI were reported. In addition, CLA feeding in dairy cows was shown to alleviate (Shingfield et al, 2004;Odens et al, 2007), as well as exacerbate (Pappritz et al, 2011), postpartum negative energy balance, whereas others reported no effect (Bernal-Santos et al, 2003;Selberg et al, 2004;Castañeda-Gutiérrez et al, 2005;Moallem et al, 2010). This variation in DMI and calculated energy balance due to CLA feeding might depend on study design (e.g., the amounts of trans-10,cis-12 CLA isomer fed or stage of lactation when CLA feeding was initiated) but suggests that CLA supplementation may not necessarily result in an improved energy status in dairy cows during early lactation.…”
Section: Effects Of Cla On Milk Performance and Body Conditionmentioning
confidence: 99%